A Comparative Analysis of Transcranial and Endoscopic Repair for Traumatic CSF Rhinorrhea - Vasu, Srivatsan Thirumalai; Krishnamoorthy, Venkidesh; Karunakaran, Sudish; Pillay, Haroon M. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Surgical treatment of anterior cranial base traumatic cerebrospinal fluid (CSF) rhinorrhea is challenging and is fraught with complications. Whether a person should be offered open craniotomy or endoscopic endonasal repair is a dilemma faced by most surgeons. This study is one of the few to directly compare the two forms of management.Methods Data were collected from two groups of 15 patients each who underwent transcranial CSF leak repair and endoscopic endonasal CSF leak repair in a tertiary care hospital over a 3-year period. Information including demographics, recurrence rates, complications, and hospital and intensive care unit (ICU) stay was recorded and analyzed. Outcome was assessed up to 6 months.Results Recurrence was seen in 9/30 patients, 6 in the transcranial group and 3 in the endoscopic group. Hospital stay was longer than 1 week in all the transcranially operated patients and only in 73% of the endoscopically operated patients (p = 0.439) although ICU stay was reduced in the endoscopic group (p = 0.066). Complications were more common with transcranial repair (seven of eight patients who underwent transcranial repair, p = 0.035) with anosmia being the most common (33.3%, p = 0.042).Conclusion The transcranial open repair is a reasonable choice especially for leaks that occur through the frontal sinus and extend backward into the frontoethmoidal region. However, this approach has the drawbacks of greater number of complications, higher recurrence rate, and longer ICU and overall hospital stay. The endoscopic endonasal repair enjoys a lower morbidity profile although it may not be an adequate treatment for leaks that are placed far laterally in the frontal sinus.
Keywords: traumatic CSF rhinorrhea; endoscopic CSF leak repair; transcranial CSF leak repair